A possible linkage between highly fractionated granitoids and associated W-mineralization in the Mesozoic Yaogangxian granitic intrusion, Nanling region, South China. (15th May 2020) - Li, Wen-Sheng; Ni, Pei; Wang, Guo-Guang; Yang, Yu-Long; Pan, Jun-Yi; Wang, Xiao-Lei; Chen, Li-Li; Fan, Ming-Sen
Graphical abstract: Highlights: The Yaogangxian granitic intrusion is a composite complex formed with ages of 161 ± 3 and 157 ± 2 Ma. Granites in the intrusion belong highly fractionated S-type variety. Melt-fluid interaction and Proterozoic W-rich wall-rocks control W mineralization. Granites and W deposits in Nanling were related to the Jurassic lithospheric extension. Abstract: The Yaogangxian (YGX) W deposit in the central Nanling W province, South China, is one of the largest W deposits worldwide. Both vein-type wolframite and skarn-type scheelite orebodies were exposed in YGX. These scheelite and wolframite mineralization are spatially associated with the YGX granitic intrusion. The exposed intrusion contains two main intrusive phases: lower zone, coarse-grained two-mica granite and upper zone, fine-grained muscovite granite. An integrated study of whole-rock geochemistry, LA ICP-MS zircon U–Pb geochronology, and zircon Hf isotopic geochemistry of the YGX granitic intrusion was undertaken to constrain its magmatic source and petrogenesis. Cassiterite LA ICP-MS U–Pb dating was also undertaken to constrain the connection between the intrusion and hydrothermal W mineralization. Zircon U–Pb dating yielded weighted-mean ages of 161 ± 3 and 157 ± 2 Ma for the two-mica and muscovite granites, respectively. Cassiterite crystals from wolframite–quartz veins display growth zonation under cathodoluminescence, and have a weighted-mean zircon U–Pb age of 158 ± 2 Ma. The formation of the muscovite granite and related W mineralization in the YGX deposit was thus initiated during the early Yanshanian. The YGX granites display typical metaluminous to strongly peraluminous characteristics with high SiO2 (73.5–79.1 wt%) and K2 O (3.0–5.0 wt%) contents. They are enriched in heavy rare earth elements (REEs) comparative to light REEs. Notably, they exhibited strong negative Eu anomalies, and are depleted in Sr, Ba, P, and Ti. In addition, muscovite granites in YGX are more significantly enriched in heavy REEs relative to light REEs than two-mica granites, indicating that the former experienced higher degree fractionation than the latter. Zircon grains of the YGX granitoids have strongly negative εHf (t) (–15 to –10.3), with two-stage Hf model ages of 2.15–1.86 Ga, indicating a magma source of reworked ancient crustal material without obvious involvement of juvenile materials. The results of petrology and geochemistry indicate that the YGX granitic intrusion is a highly fractionated S-type granite emplaced during widespread 160–150 Ma granitic magmatism in the Nanling region. Further evolution to late stage for multiphase YGX granitic intrusion is needed to enrich ore-forming elements after magmatic emplacement. It is suggested that the extensional environment of continental lithosphere caused by the northwest subduction of the paleo-Pacific plate may play an key role in the genesis of YGX S-type granite. W-rich Proterozoic basement rocks and fractional crystallization may provide material for the formation of the granite-related tungsten mineralization.